Seroprevalence and risk factors of Toxoplasma gondii infection among pregnant women in south western, Saudi Arabia - Almushait, Mona A. (Springer India, 2012)
This study aimed to determine the seroprevalence of Toxoplasma gondii in pregnant women in the south western region of Saudi Arabia and to find out the possible risk factors that may lead to infection. This cross sectional hospital based study was carried out at three hospitals in the south western region of Saudi Arabia from January 2008 to August 2010. Blood samples from 487 pregnant women were collected and used to detect anti-T. gondii antibodies IgM and IgG by enzyme linked immunosorbent assay (ELISA). A questionnaire interview was carried out to ask about some risk factors of infection. Among the 487 studied pregnant women, 38.8 % were seropositive for anti T. gondii IgG while 6.2 % were positive for anti T. gondii IgM and 3.3 % were positive for both anti T. gondii IgG & IgM. The only risk factor associated with seropositive anti T. gondii IgM was the history of the intake of immunosuppressive drugs. Regarding anti T. gondii IgG seropositivity, it was found to increase significantly with increased age, number of gravida and parities, and previous history of toxoplasmosis. The seroprevalence of T. gondii IgG & IgM by ELISA among pregnant women in the south western region of Saudi Arabia is considerable with few identifiable significant risk factors reported.